2015
DOI: 10.4103/1687-4625.155666
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and coronary artery disease in young Egyptians presenting with acute coronary syndrome

Abstract: ResultsThe metabolic risk score was determined; patients with a significant metabolic score of at least 3 risk score constituted 66.4% of the total cohort (n = 81 patients).Patients were subjected to coronary angiography. Totally occluded vessels were found in 33.3% of metabolic syndrome patients and in 26.8% of non metabolic syndrome patients (P < 0.05). The SYNTAX score was used to assess the severity of CAD; it was found to be statistically significantly higher in patients with metabolic syndrome than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
5
2
Order By: Relevance
“…This is consistent with a study carried by Hassanin et al [28]. This similarity implies that age is not a significant risk factor in patients with MetS.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with a study carried by Hassanin et al [28]. This similarity implies that age is not a significant risk factor in patients with MetS.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, prevalence of Hypertension was 23%. A recent study done in Egypt in young metabolic syndrome patients, it was found that CAD and acute coronary syndrome weremore severe in this group of patients who are known cases of obesity, hyperlipidemia and DM [20]. Diabetes and hyperlipidemia are common among young CAD patients.…”
Section: Discussionmentioning
confidence: 74%
“…A study in Framingham, Massachusetts concluded that total cholesterol, blood pressure, and LDL cholesterol are predictors for CHD in the middle-aged white population [18]. In addition to the previous predictors, old age, male sex, low HDL-C, diabetes are associated with altered CHD events in patients with low LDL-C, according to MESA (Multi-Ethnic Study of Atherosclerosis) by the American College of Cardiology Foundation [19].…”
Section: Discussionmentioning
confidence: 99%